2020
DOI: 10.1155/2020/5871980
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity Predicts Childhood Undernutrition: A Cross-Sectional Study in West Oromia (Ethiopia)

Abstract: Background. Despite mixed reports, food insecurity emerges as a predictor of nutritional status, assumably limiting the quantity and quality of dietary intake. In Ethiopia, the prevalence of childhood undernutrition and food insecurity is highly pronounced. However, whether household food insecurity predicts undernutrition in children was not yet well established. Thus, the aim of the present study was to identify the link between household food access and undernutrition in children aged 6–23 months in West Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
6
14
0
Order By: Relevance
“…This finding was consistent with a study conducted in the Tigray region of Ethiopia, which showed that the prevalence of stunting and wasting among children in household food insecurity was 52.1% and 12.6%, respectively [ 28 ]. It also agreed with a study conducted in west Oromia, which showed that the prevalence of stunting and wasting among children in food-insecure households was 41.8% and 14.9%, respectively [ 29 ]. A similar report in South Ethiopia showed that the prevalence of stunting and wasting among children in household food insecurity was 45.6% and 14.6%, respectively [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with a study conducted in the Tigray region of Ethiopia, which showed that the prevalence of stunting and wasting among children in household food insecurity was 52.1% and 12.6%, respectively [ 28 ]. It also agreed with a study conducted in west Oromia, which showed that the prevalence of stunting and wasting among children in food-insecure households was 41.8% and 14.9%, respectively [ 29 ]. A similar report in South Ethiopia showed that the prevalence of stunting and wasting among children in household food insecurity was 45.6% and 14.6%, respectively [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that children from food-insecure households are at a higher risk of under-nutrition. Similar findings from west Oromia of Ethiopia indicate that household food insecurity is significantly associated with the under-nutrition of children [ 38 ].…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, a study conducted in the United States in 2007 showed that only 11% of the population had food insecurity (49). In our study, similar to other studies (40,50), a significant association was found between malnutrition in children and the household security status. Also, national food availability, measured as dietary energy supply per capita, was reported as a very important factor affecting the prevalence of childhood malnutrition (40).…”
Section: Association Of Malnutrition In Children With the Family's Food Security Statussupporting
confidence: 93%